When winning is losing: A randomized controlled trial testing a video game to train food-specific inhibitory control. (1st October 2018) - Poppelaars, Anouk; Scholten, Hanneke; Granic, Isabela; Veling, Harm; Johnson-Glenberg, Mina C.; Luijten, Maartje
Abstract: Overweight and obesity are major causes of worldwide morbidity and mortality. A two-armed randomized controlled trial ( n = 104) examined the effectiveness of Hit n Run, a video game based on the principles of Go/No-Go inhibition training, in young adults who reported disinhibited eating. Adults (aged 18 to 30) were randomly assigned to play Hit n Run or received an informative brochure ( Healthy Eating Step by Step ; HESbS). Prior to and directly following the intervention week general and food-specific inhibitory control, caloric intake, and perceived attractiveness of food pictures were assessed. Results revealed no improvements in food-specific inhibitory control or caloric intake in either intervention group. Similar improvements for general inhibitory control and similar decreases in perceived attractiveness of food-related stimuli were observed for both Hit n Run and HESbS. Future research should aim to clarify how video game design can implement working mechanisms of cognitive training tasks to facilitate the development of effective game-based interventions.